2022
DOI: 10.3389/fpsyg.2022.895446
|View full text |Cite
|
Sign up to set email alerts
|

Stair walking effects on feelings of energy and fatigue: Is 4-min enough for benefits?

Abstract: PurposeEven low intensity exercise bouts of at least 15 min can improve feelings of energy (FOE) and reduce systolic blood pressure. However, little is known about the psychological outcomes of briefer exercise bouts, particularly for modes of exercise that are more intense than level walking, and readily available to many working adults. This study assessed the effects of a 4-min bout of stair walking on FOE and feelings of fatigue (FOF).MethodsThirty-six young adult participants were randomized to either sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It has been shown that a single bout of physical activity can impact both mood [16][17][18] and cognition [19] positively; however, the duration and type of physical activity both influence the magnitude of the effect. Recently, a study by Carmichael and colleagues [20], reported that four minutes of stair walking did not modify feelings of energy and fatigue. Unfortunately, this study did not measure any other mood states.…”
Section: Introductionmentioning
confidence: 96%
“…It has been shown that a single bout of physical activity can impact both mood [16][17][18] and cognition [19] positively; however, the duration and type of physical activity both influence the magnitude of the effect. Recently, a study by Carmichael and colleagues [20], reported that four minutes of stair walking did not modify feelings of energy and fatigue. Unfortunately, this study did not measure any other mood states.…”
Section: Introductionmentioning
confidence: 96%